The public relations writer's handbook - Lehmann, Whitney (Whitney S.) (New York, NY Routledge, Taylor & Francis Group, 2020)
From pitches and press releases to news and feature stories to social media writing and more, this new book by author Whitney Lehmann and a handful of experienced contributors breaks down the most widely used types of public relations writing needed to become a PR pro.

The Public Relations Writer’s Handbook serves as a guide for those both in the classroom and in the field who want to learn, and master, the style and techniques of public relations writing. Eighteen conversational chapters provide an overview of the most popular forms of public relations writing, focusing on media relations, storytelling, writing for the web/social media, business and executive communications, event planning and more. Chapters include user-friendly writing templates, exercises and AP Style skill drills and training.

Whether you’re a PR major or PR practitioner, this book is for you. Lehmann has combined her industry and classroom experience to create a handbook that’s accessible for PR students and practitioners alike.
Purpose, process, style, form and tone -- News releases and other types of releases -- Media pitches -- Media advisories/alerts -- Public service announcements -- Media kits -- Interviewing -- Background materials and backgrounders -- Fact sheets -- Bio sketches -- News writing -- Feature writing -- Email and writing for the web -- Writing for social media -- Letters and memos -- Speech writing -- Talking points and run of show -- Shot lists and photo captions.
Includes bibliographical references and index.
Keywords: Public relations; Business writing